Case studies in combining sequence analysis and modelling - Mervi Eerola (Springer, 2022)
This methodological paper presents three case studies of life course analysis
in which the clustering of the sequences and probabilistic modelling have been
combined or contrasted when analysing a particular research question. Latent variable
hierarchical modelling is used in various ways to account for correlation in
multidimensional response variables and to model underlying structures in the life
course. We conclude that, while sequence analysis allows to use multidimensional
and time-dependent criteria either for comparing life patterns of groups of individuals
or to extract subgroups for further analysis, the SA outcome may be rather
unspecific for causal-like questions.
Sequence Analysis and Related Approaches: Innovative Methods and Applications